2019
DOI: 10.1115/1.4043990
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Dynamics of Cable-Harnessed Structures: Experimental Validation

Abstract: The experimental study and model validations for the coupled dynamics of a cable-harnessed beam structure are presented. The system under consideration consists of multiple pretensioned cables attached along the length of the host beam structure positioned at an offset distance from the beam centerline. Analytical model presented by the coupled partial differential equations (PDEs) for various coordinates of vibrations is found, and the displacement frequency response functions (FRFs) obtained for both Euler–B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…For the periodic pattern case, n f is varied. e system parameters are from Table 3 and are similar to our experimental characterization [16]. For the OP modes, when the straight cable with offset case and the n f � 5 periodic pattern case are compared, the coupling effects are slightly lower for n f � 5 case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the periodic pattern case, n f is varied. e system parameters are from Table 3 and are similar to our experimental characterization [16]. For the OP modes, when the straight cable with offset case and the n f � 5 periodic pattern case are compared, the coupling effects are slightly lower for n f � 5 case.…”
Section: Resultsmentioning
confidence: 99%
“…e coefficients are a function of beam and cable parameters [19]. In these energy expressions, the terms higher than second order are ignored considering the small-scale vibrations.…”
Section: Development Of Energy Expressions Considering the Coupling Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The review suggested that future improvements in analytical models of tower-line systems are motivated and expected. Yerrapragada and Salehian (2019) studied the coupled dynamics of a cable-harnessed structure by analytical modeling, verifying the frequency response function (FRF’s) through experiments. Gattulli et al (2019) studied the cable and beam nonlinear interaction in a beam–cable–beam system.…”
Section: Introductionmentioning
confidence: 99%